Pasture-associated Liver Disease in Horses: VM180/VM180, 8/2011 - House, Amanda M.; Elfenbein, J. R. (EDIS, 2011)
Know the common pasture plants that cause liver disease, because clinical signs are often non-specific and may not appear until it is too late. This 4-page fact sheet was written by A.M. House and J.R. Elfenbein and published by the UF Department of Veterinary Medicine-Large Animal Clinical Sciences, August 2011. (Photo: Thomas Wright)